2009
DOI: 10.1264/jsme2.me08537
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Amount of Cellular Trehalose, the Activity of Maltooligosyl Trehalose Hydrolase, and the Expression of Its Gene in Response to Salt Stress in the Cyanobacterium Spirulina platensis

Abstract: The amount of trehalose in cells of the cyanobacterium Spirulina (Arthrospira) platensis increased rapidly when a high concentration of NaCl was added to the culture medium. Inhibition of sodium ion transport by amiloride and monensin significantly decreased the amount of cellular trehalose, suggesting that the influx of sodium ions into the cells is coupled with the accumulation of trehalose. The amount of maltooligosyl trehalose hydrolase (Mth) which produces trehalose from maltooligosyl trehalose increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In the subsequent step, the terminal disaccharide is cleaved by the maltooligosyltrehalose trehalohydrolase (Mth, EC 3.2.1.141) encoded by treZ . Similar proteins involved in Tre synthesis have also been found in the related strain Nostoc punctiforme IAM M‐15 (Yoshida and Sakamoto, 2009) and in Arthrospira ( Spirulina ) platensis NIES‐39 (Ohmori et al ., 2009) and are present in the genomes of many other cyanobacteria (Table 1). In addition, homologues of a maltose glucosylmutase that converts maltose to Tre [= trehalose synthase (TreS), EC 5.4.99.16, Nishimoto and colleagues 1996] are also present in many cyanobacterial genomes (Table 1).…”
Section: Biochemical and Molecular Basis For Compatible Solute Accumusupporting
confidence: 57%
See 1 more Smart Citation
“…In the subsequent step, the terminal disaccharide is cleaved by the maltooligosyltrehalose trehalohydrolase (Mth, EC 3.2.1.141) encoded by treZ . Similar proteins involved in Tre synthesis have also been found in the related strain Nostoc punctiforme IAM M‐15 (Yoshida and Sakamoto, 2009) and in Arthrospira ( Spirulina ) platensis NIES‐39 (Ohmori et al ., 2009) and are present in the genomes of many other cyanobacteria (Table 1). In addition, homologues of a maltose glucosylmutase that converts maltose to Tre [= trehalose synthase (TreS), EC 5.4.99.16, Nishimoto and colleagues 1996] are also present in many cyanobacterial genomes (Table 1).…”
Section: Biochemical and Molecular Basis For Compatible Solute Accumusupporting
confidence: 57%
“…Combined protein with putative TpS and TpP activity. (p) – postulated from gene occurrence; (a) – own preliminary measurements; (b) –Klähn and colleagues (2010); (c) –Warr and colleagues (1985a); (d) –Ohmori and colleagues (2009); (e) –Higo and colleagues (2006); (f) –Reed and Stewart (1985).…”
Section: Introductionmentioning
confidence: 99%
“…PCC 8005 cells rerouted their carbon metabolism to synthesis of storage molecules in the form of trehalose and polyhydroxyalkanoate (PHA). Several reports suggest the contribution of trehalose in response to high salt stress [ 8 ], and in desiccation tolerance by protecting the cells and proteins from oxygen radicals [ 40 ]. Recently Webb and co-worker suggested a possible role of trehalose as an efficient protectant of protein activity (enzymes) against irradiation, either alone or in combination with Mn 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…The resilience of Arthrospira cells to extreme environmental conditions was reported. It has the ability to grow in highly alkaline environments [ 7 ], environments with high salt concentration: 1.5 higher than sea, ranging between 20 to 30 g L -1 [ 8 ], at extreme temperatures lower than 15°C and higher than 45°C [ 9 ], and at high light intensities as 500 μE/m 2 /s [ 10 ]. It is also able to resist ionising radiation from UV and gamma rays, as well as charged particles [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 Moreover, molecular analysis of adenylate cyclase genes has shown that A. platensis develops a number of diverse cAMP-dependent signal cascades to adapt to different severe environmental conditions. 1214 …”
Section: Introductionmentioning
confidence: 99%